FOLK BELIEF AND TRADITIONS OF THE SUPERNATURAL: A CASE STUDY OF SHIMLA HILLS IN WESTERN HIMALAYAS - Vikram Bhardwaj (European Scientific Journal, ESJ, 2015)
This paper intends to highlight the belief in the existence of superhuman or supernatural power in the area of study, which has a rich stock of myths, legends, traditions and the sacred occasion which are explained by some myth or the other, having some mythology behind them. Shimla hills as a part of Western Himalayas has plenty of folk beliefs and legends associated with deities’ heroes and cults, and these play an important role in the customary practice and behaviour of the masses. The region has several great deities drawn from historical traditions. These gods and heroes, and the folklore associated with them are the guardians of the traditional value system which governs the life of the people in this area. This unique amalgamation of good and evil spirits as gods has tremendous effect on the social and religious culture of the people residing in the region. Most of the gods have their family members as deities of various villages, which have given birth to strong connections within the region in terms of social and political relationships. While these project a sense of monolithic culture, it is also possible to read the sources and complexity of the cultural formation through an analysis of the conflicts and contestations within the tradition variation. These folk beliefs, traditions of the supernatural are the mirror of the cultural life of this area which can be described as animistic.